Food safety : past, present, and predictions - Detwiler, Darin S. (Academic Press, an imprint of Elsevier, 2020)
Food Safety: Past, Present, and Predictions offers a multidisciplinary approach on major food industry regulatory compliance changes that have emerged since the landmark 1993 E.coli outbreak. The book is broad in coverage, providing a look back at 25 years of change in order to better conceptualize the future of effective and sustainable food safety compliance efforts and technologies. Historical case studies and technological developments are written by experts and those who played key roles in events. Topics are explained in a way that not only helps improve industry and consumer awareness, but also offers tools to improve education and communication. -- Provided by publisher.
Characteristics of states with ideal food policies
Keywords: Food -- Safety measures.; Food industry and trade -- Safety measures.; elektronické knihy; electronic books